Association between serum oxidative stress indicators, inflammatory indicators and suicide attempts in adolescents with major depressive disorder - Peng, Cao; Xu, Mengting; Ye, Meng; Yang, Weiwei; Fang, Maosheng (Frontiers in Psychiatry, 2025)
BackgroundProgress in research on the neurobiology of suicide behavior in adolescents has notably lagged compared to that of adults. This study aimed to investigate the associations between serum indicators, including oxidative stress (OS) and inflammatory indicators, and psychological factors with suicide attempts (SA) in adolescents with major depressive disorder (MDD) while also exploring potential markers.MethodsThis study involved the psychological assessment of 106 first-time hospitalized adolescents aged 12 to 18 with MDD and the measurement of serum indicators. Participants were categorized into two groups according to their history of SA within the preceding six months. Screening the best markers for suicide by machine learning algorithms. Multivariable logistic regression was used to assess the correlation between these indicators and suicide. Secondly, Mendelian randomization (MR) was used to initially explore the causal relationship between these serum indicators and suicide.ResultsIn adolescents diagnosed with MDD, those who had attempted suicide exhibited elevated serum superoxide dismutase (SOD) activity, reduced nitric oxide (NO) levels, more severe anxiety and depressive symptoms, worse sleep quality, increased exposure to adverse life events, less effective coping strategies, worse parental attachment, more severe alexithymia, and more impulsivity when compared to their counterparts without a history of SA (all p<0.05). The multivariable analyses showed a significant association between serum SOD activity (OR 1.254, 95% CI 1.043-1.534) and anxiety symptoms (OR 1.056, 95% CI 1.020-1.097) with SA in adolescents diagnosed with MDD. The MR analyses showed a causal association between genetically determined low uric acid (UA) levels and a higher risk of SA (OR 0.942 95%CI 0.896-0.991).ConclusionSerum SOD activity, anxiety symptoms, and UA levels may be potential markers of SA and suicide intent in adolescents with MDD.